2010
DOI: 10.1158/1541-7786.mcr-10-0114
|View full text |Cite
|
Sign up to set email alerts
|

CADPE Inhibits PMA-Stimulated Gastric Carcinoma Cell Invasion and Matrix Metalloproteinase-9 Expression by FAK/MEK/ERK–Mediated AP-1 Activation

Abstract: Metastasis is one of the main causes of death for patients with malignant tumors. Aberrant expression of matrix metalloproteinase-9 (MMP-9) has been implicated in the invasion and metastasis of various cancer cells. Here, we found that caffeic acid 3,4-dihydroxy-phenethyl ester (CADPE) could inhibit the migration and invasion of human gastric carcinoma cells in Transwell migration assays. To understand the underlying mechanism, we showed that CADPE significantly inhibited phorbol 12-myristate 13-acetate (PMA)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 46 publications
2
46
0
Order By: Relevance
“…Therefore, regulation of MMP-9 expression in cancer development has been of interest. Although the exact regulatory mechanism of MMP-9 expression in cancer is not clear, MMP-9 expression can be induced by various stimuli, including endothelial growth factor, IL-1␣, TNF-␣, LPS, and 12-O-tetradecanoylphorbol-13-acetate (7,39,40). The promoter region of the human MMP-9 gene contains multiple functional cis-regulatory regions, including binding sites for CREB, AP-1, NF-B, Sp-1, and Ets-1 within the minimal 670-bp MMP-9 promoter, and these sites are critical for the transcriptional activation of MMP-9 that is involved in basal and induced transcriptional responses (11,35,38,41).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, regulation of MMP-9 expression in cancer development has been of interest. Although the exact regulatory mechanism of MMP-9 expression in cancer is not clear, MMP-9 expression can be induced by various stimuli, including endothelial growth factor, IL-1␣, TNF-␣, LPS, and 12-O-tetradecanoylphorbol-13-acetate (7,39,40). The promoter region of the human MMP-9 gene contains multiple functional cis-regulatory regions, including binding sites for CREB, AP-1, NF-B, Sp-1, and Ets-1 within the minimal 670-bp MMP-9 promoter, and these sites are critical for the transcriptional activation of MMP-9 that is involved in basal and induced transcriptional responses (11,35,38,41).…”
Section: Discussionmentioning
confidence: 99%
“…(21) Caffeic acid 3,4-dihydroxy-phenethyl ester (CADPE), a compound originally isolated from medicinal plants Sarcandra glabra and Teucrium pilosum, (22) has attracted much interest due to its proven pharmacologic safety and its many biologic activities, such as induction of cancer senescence, (23) inhibition of tumor angiogenesis, (24) suppression of hepatocellular carcinoma growth, (25) and gastric carcinoma cell migration. (26) In the present study, we investigated the effects of CADPE on osteoclastogenesis both in vitro and in vivo, and elucidated the underlying molecular mechanisms. We found that CADPE suppressed RANKL-induced osteoclast differentiation within non-growth inhibitory concentrations at an early stage of osteoclastogenesis.…”
Section: Introductionmentioning
confidence: 97%
“…Effects of CTXA on PMA-stimulated phosphorylation of p38MAPK, ERK1/2, and JNK Previous studies have reported involvement of p38MAPK, ERK1/2, and JNK in cytokine-induced EPCR shedding, and increased phosphorylation of p38MAPK, ERK1/2, and JNK was known to occur by stimulation with PMA (Leng et al 2004;Menschikowski et al 2009;Han et al 2010). Therefore, in order to determine the molecular mechanisms of suppression of PMA-induced EPCR shedding by CTXA, the effects of CTXA on PMA-stimulated phosphorylation of p38MAPK, ERK1/2, and JNK were tested.…”
Section: Effect Of Ctxa On Clp-induced Epcr Sheddingmentioning
confidence: 99%
“…Increased phosphorylation of p38MAPK, ERK1/2, and JNK is known to occur by stimulation with PMA (Leng et al 2004;Menschikowski et al 2009;Han et al 2010), and activation of TACE occurs upon activation of ERK or p38 MAPK (Huovila et al 2005;Murphy 2008); therefore, in order to define the processes responsible for inhibition of PMA-stimulated shedding of EPCR and expression of TACE by CTXA, we investigated involvement of MAPK signaling pathways in PMA-stimulated condition. MAPKs comprise a family of highly conserved serine/threonine protein kinases, which are believed to have key roles in mediation of inflammation (Thalhamer et al 2008).…”
Section: Effect Of Ctxa On Clp-induced Epcr Sheddingmentioning
confidence: 99%
See 1 more Smart Citation